2018
DOI: 10.1186/s13089-018-0090-7
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of cardiac ultrasound performance by general internal medicine physicians during a 6-month faculty development curriculum

Abstract: BackgroundPoint-of-care (POCUS) education is rapidly expanding within medical schools and internal medicine residency programs, but lack of trained faculty is a major barrier. While POCUS training can improve short-term outcomes, knowledge and skills rapidly decay without deliberate practice and feedback. The purpose of this study was to evaluate the performance of focused cardiac ultrasound (FCU) by volunteer general internal medicine (GIM) faculty participating in a longitudinal POCUS curriculum.MethodsParti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…An important consideration when designing a training program is the prevention of skill decay, which has been noted to occur rapidly (within 1-3 months) after the completion of a brief training program [62]. One study [56] found that learners retained their imaging skills at 6 months post-training, but there was no data on skill retention beyond 6 months in any included studies. The duration of the training phase may be inversely related to the rate of decay, suggesting that longitudinal support through deliberate practice and mentored review may help learners to retain their skills [56].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An important consideration when designing a training program is the prevention of skill decay, which has been noted to occur rapidly (within 1-3 months) after the completion of a brief training program [62]. One study [56] found that learners retained their imaging skills at 6 months post-training, but there was no data on skill retention beyond 6 months in any included studies. The duration of the training phase may be inversely related to the rate of decay, suggesting that longitudinal support through deliberate practice and mentored review may help learners to retain their skills [56].…”
Section: Discussionmentioning
confidence: 99%
“…One study [56] found that learners retained their imaging skills at 6 months post-training, but there was no data on skill retention beyond 6 months in any included studies. The duration of the training phase may be inversely related to the rate of decay, suggesting that longitudinal support through deliberate practice and mentored review may help learners to retain their skills [56]. By making ultrasound devices readily available and easily accessible within clinical environments, physicians can develop ways to incorporate FoCUS into their daily practice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations